2014
DOI: 10.1097/wnr.0000000000000228
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-dependent effects of transcranial pulsed current stimulation on interhemispheric connectivity

Abstract: Defining optimal parameters for stimulation is a critical step in the development of noninvasive neuromodulation techniques. Transcranial pulsed current stimulation (tPCS) is emerging as another option in the field of neuromodulation; however, little is known about its mechanistic effects on electrical brain activity and how it can modulate its oscillatory patterns. The aim of this study was to identify the current intensity needed to exert an effect on quantitative electroencephalogram (qEEG) measurements. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 16 publications
3
27
0
Order By: Relevance
“…Our findings included: (a) bimastoid tPCS can enhance mainly the power spectrum of the alpha bandwidth in the frontocentral and parieto-occipital brain regions compared with the other montages and (b) for the ear-clip montage, we observed an increase in theta interhemispheric coherence for the frontal area, supporting previous studies [13]. These findings suggest that a single session of tPCS has a consistent impact on cortical activity, as measured by EEG-derived connectivity, for the alpha domain and that specific electrophysiological parameters can be elicited by particular electrode montages, making tPCS a technique in which top-down (high internal processing) and bottom-up (low internal demands) processes could be targeted independently.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings included: (a) bimastoid tPCS can enhance mainly the power spectrum of the alpha bandwidth in the frontocentral and parieto-occipital brain regions compared with the other montages and (b) for the ear-clip montage, we observed an increase in theta interhemispheric coherence for the frontal area, supporting previous studies [13]. These findings suggest that a single session of tPCS has a consistent impact on cortical activity, as measured by EEG-derived connectivity, for the alpha domain and that specific electrophysiological parameters can be elicited by particular electrode montages, making tPCS a technique in which top-down (high internal processing) and bottom-up (low internal demands) processes could be targeted independently.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that the mechanism of tPCS relies on the introduction of a random frequency able to entrain the intrinsic neural oscillations within the range of the applied frequency [1,2]. tPCS delivered at an intensity of 2 mA with a randomly generated frequency ranging between 6 and 10 Hz during 20 min induces reliable electrophysiological changes in the brain [13]. The effects of tPCS on brain coherence and connectivity suggest that tPCS can alter cognitive functioning [4] and thus be a promising tool to treat neuropsychiatric disorders in which abnormal oscillatory patterns have been identified [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…We calculated interhemispheric coherence for these bands and sub-bands, using two different electrode pairs: E19–E56 and E14–E57, located in the frontotemporal area and including their reciprocal location in the contralateral hemisphere, as described in recent tPCS trials [1618,21]. Welch’s averaged modified periodogram method was used to find the estimated coherence of signal x and y, representing each electrode site.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, computer modeling [15] and neuropshysiological studies (using quantitative electroencephalography – QEEG) have shown that tPCS can modulate frontal [16] and interhemispheric [17] neuronal connectivity. Regarding the optimal parameters of stimulation, previous studies have shown that a current of 2 mA during 20 min [18] at a random frequency between 6 and 10 Hz [17] induce the most significant neurophysiological effects, especially increasing power in the alpha band, when compared to lower and higher frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, interhemispheric connectivity can also be enhanced by application of tDCS. Interhemispheric functional connectivity, as measured by quantitative EEG (qEEG) parameters in healthy volunteers increased following a single session of tDCS (Castillo Saavedra et al, 2014; Morales-Quezada et al, 2014). As a measure of interhemispheric connectivity, these reports analyzed the level of interhemispheric coherence which is defined as a linear relationship between the specific frequency waves (alpha, beta, and theta waves) between the two hemispheres.…”
Section: Interhemispheric Connectivity In Dbs Studiesmentioning
confidence: 99%